Safety and health in the construction industry: an approach to collective protection measures (Research, Society and Development, 2020)
The construction industry represents, for Brazil, one of the business sectors with the highest absorption of labor, in addition to being one of the greatest economic powers, with great generation of job opportunities. It is a segment characterized by improvisation combined with low qualification of workers, poor use of security measures, in addition to discontinuity of the process, with mobilization and demobilization of the teams at each work performed. These situations experienced by the sector can result in the compromise of the physical integrity of the worker, with injuries and illnesses, these being the great challenges found in the works. Through a literature review and survey of construction companies with satisfactory safety and health performance at work, the aim of that study is to present an analysis on the use of collective protection measures, emphasizing the importance of prevention as a priority. This prevention must start in the planning of the work, with a focus on an adequate classification and selection of collective protections and an effective qualification process for the providers of these protections. As a result, more effective and consistent alternatives for actions are presented that provide a safer and healthier work environment for workers working on construction sites.